Burkholderia cepacia strain IrV1 multi-resistant to copper and dyes isolated from laboratory wastewater effluent - WAHYU IRAWATI; VALENTINE LINDARTO; REINHARD PINONTOAN; TRIWIBOWO YUWONO; FEBRI MANGOMO MANGUNSONG; DESTYA WATY SILALAHI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Irawati W, Lindarto V, Pinontoan R, Yuwono T, Mangunsong FM, Silalahi DW. 2022. Burkholderia cepacia strain IrV1 multi-resistant to copper and dyes isolated from laboratory wastewater effluent. Biodiversitas 23: 2614-2620. Copper and dye multi-resistant bacteria may be cultivated to increase the efficiency of waste bioremediation processes. Multi-resistant bacteria can be isolated from waste containing copper and dyes, including laboratory waste. The aims of this study were to: (i) isolate copper-resistant bacteria from wastewater, (ii) determine the multi-resistance of bacteria against copper and dyes, and (iii) observe the ability of bacteria to remove colors methylene blue, basic fuchsin, and Congo red. Selected bacterial isolates were identified based on the 16S rDNA gene. One highly copper resistant bacterial strain IrV, showed resistance to 7 mM CuSO4, 100 ppm methylene blue, 100 ppm basic fuchsin, and 100 ppm Congo red. Based on the 16S rDNA gene sequence, strain IrV belongs to Burkholderia cepacia with 99.86% similarity. The addition of copper on the medium resulted in colony color changes from light yellow to green indicated Cu binding within the cell. Moreover, a clear zone around the colony was observed, suggesting that the strain is capable of decolorizing methylene blue, Congo red, and basic fuchsin dyes. The results thus demonstrate that bacterial strain IrV is multi-resistant to copper and dyes.